X+6+ax-9=3x+b

Simple and best practice solution for X+6+ax-9=3x+b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+6+ax-9=3x+b equation:


Simplifying
X + 6 + ax + -9 = 3x + b

Reorder the terms:
6 + -9 + X + ax = 3x + b

Combine like terms: 6 + -9 = -3
-3 + X + ax = 3x + b

Reorder the terms:
-3 + X + ax = b + 3x

Solving
-3 + X + ax = b + 3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + X + 3 + ax = b + 3 + 3x

Reorder the terms:
-3 + 3 + X + ax = b + 3 + 3x

Combine like terms: -3 + 3 = 0
0 + X + ax = b + 3 + 3x
X + ax = b + 3 + 3x

Reorder the terms:
X + ax = 3 + b + 3x

Add '-1ax' to each side of the equation.
X + ax + -1ax = 3 + b + -1ax + 3x

Combine like terms: ax + -1ax = 0
X + 0 = 3 + b + -1ax + 3x
X = 3 + b + -1ax + 3x

Reorder the terms:
X = 3 + -1ax + b + 3x

Simplifying
X = 3 + -1ax + b + 3x

See similar equations:

| 9/3=n/9 | | 5/9=x/30 | | 18=k/3-2 | | 3x+8-9x=2x-16 | | -7(3x-7)+7x=14 | | 6.1(3.1+2.5)=15.3-3.9 | | 0.75x-12=0.5x-6 | | 7(3g+5K)-14g+12= | | 2b+2b=-16 | | 8-(1/2)y=-6 | | -3x-1=21 | | 0.75-12=0.50-6 | | B+4=3 | | 42x+21=90 | | 3m(2m+3)=0 | | 0.75+n=2 | | -8t^2+4t+12=0 | | ln(x)-ln(13)=0 | | -65/50 | | -3x+-1+-2=-9 | | 7x-4=5x-46 | | 50y/50 | | 108-1-4y=0 | | 50/50y= | | 2.48/4=x | | 9x+4-2x-2=16 | | .4x-(x+.3333333333)=.06666666666(x+1) | | 4(f+3)=17+4f | | -13b+b=31 | | 15x-35+-8x-36=43 | | x^3-250=0 | | 5(10^3)/15(10^2) |

Equations solver categories